The Role of Physical Activity in Asthma Outcomes: A Review of Recent Studies: Physical Activity and Asthma Outcomes - A Review - Mikszta, Jakub; Mikszta, Natalia; Lorenc, Tomasz; Michalik, Maciej; Muras, Mateusz; Marcinkowski, Krzysztof; Marcinkowska, Julia (Quality in Sport, 2025)
Purpose of Research Bronchial asthma is a chronic disease with a growing global prevalence, significantly affecting public health and quality of life. This review aims to synthesize evidence on the effects of physical activity, a non-pharmacological intervention, on asthma control, pulmonary function, inflammation, and overall well-being. Research Materials and Methods To conduct this review, a systematic literature search was performed in the PubMed database, covering studies published within the past six years. The search was conducted using the following keywords: Asthma outcomes, Physical activity and asthma, Exercises and asthma, Asthma pathophysiology, Non-pharmacological interventions in asthma. Original clinical studies, meta-analyses, and systematic reviews assessing the impact of physical activity on asthma progression were included. The analysis encompassed studies investigating both physiological and psychosocial effects of regular physical activity in asthma patients. The final selection of publications was based on their methodological quality and relevance to the scope of this study. Basic Results Regular physical activity improves cardiorespiratory fitness, reduces airway inflammation, and enhances quality of life in asthma patients. Aerobic and interval training, along with breathing exercises, may reduce the need for inhaled corticosteroids, minimizing medication side effects. Despite concerns about exercise-induced bronchoconstriction, tailored exercise programs are safe and well-tolerated. Conclusions Physical activity should be integral to asthma management due to its positive effects on asthma control and quality of life. Future research should focus on optimizing exercise modalities and their long-term impact on disease progression.